FULFILLMENT OF CONSTITUIONAL RIGHTS OF BELIEFS PARAMASAN UPPER PRIMARY SCHOOL STUDENTS - yati, Rahmi (Universitas Lambung Mangkurat, 2024)
This classroom action research aims to increase students' interest in learning geography on the subject of the biosphere through cooperative learningstudent teams achievement divisions (STAD) in class XI IPS students at Al-Hidayah Islamic High School.Class research procedures are carried out through a flow process consisting of 4 stages, namely: 1) preparation; 2) planning; 3) implementation; 4) observation and monitoring; 5) reflection; 6) evaluation and revision. Based on the results of the questionnaire, it was found that the percentage increase in the interest score in learning geography in each cycle, the average percentage score of interest in learning geography before the action (initial) was 65.22% and was in the